PERANAN PANGHULU ADAT DALAM PENYELESAIAN SENGKETA TANAH ULAYAT DI BALAI POLAM KOTO NAN IV PAYAKUMBUH - Gusril Basir; Failin Failin (Ensiklopedia Research and Community Service Review, 2026)
The role of the customary Panghulu in resolving customary land disputes that occur. Where the customary Panghulu provides a solution to resolve the problems faced by the conflicting communities due to customary land disputes, so that the problems that occur do not continue, let alone cause conflict between the two disputing parties. Efforts to resolve customary land disputes that occur within an association, all parties handle the problem through deliberation with the assistance of the Customary Panghulu as a mediator and peace judge who will help both parties make decisions and restore balance within the association.Keywods: Role, Customary Head, Settlement, Customary Land Disputes